1972
DOI: 10.1007/bf00036764
|View full text |Cite
|
Sign up to set email alerts
|

Breaking breeding barriers in Lycopersicon. 3. Inheritance of self-compatibility in L. peruvianum (L.) Mill.

Abstract: SUMMRY brief survey is given of the genetics of self-compatibility in species with a one-locus gametophytic system of incompatibility . study has been made of the genetics of the self-compatibility found in L. peruvianum . From the results of various test crosses and selfings and of cytological research it isconcluded that self-compatibility in L . peruvianum can be based on different types of S-allele mutations, on addition of an S-allele bearing chromosome fragment, or on genes modifying the S-allele express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…InterspeciJicpollen tube growth inhibition andself-incompatibility In the L. peruvianum material studied the self-compatibility is based on mutated S-alleles or on genes modifying the S-allele action (HOGENBOOM, 1972b). In some of the lines used, obtained by selfing of self-compatible plants, one intact S-allele may Euphytica 21 (1972) 411 be present and active; besides mutated S-alleles will be present.…”
Section: Influence Of Internal or External Environmentmentioning
confidence: 99%
“…InterspeciJicpollen tube growth inhibition andself-incompatibility In the L. peruvianum material studied the self-compatibility is based on mutated S-alleles or on genes modifying the S-allele action (HOGENBOOM, 1972b). In some of the lines used, obtained by selfing of self-compatible plants, one intact S-allele may Euphytica 21 (1972) 411 be present and active; besides mutated S-alleles will be present.…”
Section: Influence Of Internal or External Environmentmentioning
confidence: 99%
“…The sudden and unreproducible seed productions after selfing in their material closely agree with our results, although the numbers of seeds per pollinated flower in our material were generally smaller . Later more indications were found that indeed generation of new S-alleles occurs in this material (HOGENBOOM, 1972) . After mutagenic treatment of seed of an S 1 S3 -population of L .…”
Section: Experiments With Clonesmentioning
confidence: 99%
“…The SI system in L. peruvianum has been classified as a gametophytic rather than sporophytic type since its pollen phenotype is determined by the genotype of the individual microspore rather than that of the pollen-producing plant (Lamm 1950). The genetic control of SI in L. peruvianum appears to be monofactorial (Lamm /950;McGuire and Rick 1954;Martin 1961 ;Hogenboom 1972c;Tanksley and Loaiza-Figueroa 1985), though the capability to fully manipulate this trait remains elusive.…”
Section: Introductionmentioning
confidence: 99%